THE EFFECT OF SELF-LEARNING ON WORK CULTURE - Debora, Debora (EARR (Educational Administration Research and Review), 2017)
The teacher is very crucial in a school with his/her competence. Especially, the teacher of tasks and roles can not be replaced even in today’s technological era. Thus, the teacher must have a good self-learning that supports the competence and capacity as a teacher. Work culture can affect how a person's work. This work of people can not be separated from his/her capacity and competence. good working culture and ugly not be separated from one's  self-learning.In this study was to investigate the effect of Self-Learning teacher's on Work Culture. The data were collected through participant observation using questionnaire with five options following Likert’s Scale 1-5. The participants were 74 of teachers from 7 different vocational schools in Palangka Raya city. Using testing path analysis test to indicated the effect of Self-Learning Teachers’ on Work Culture. Therefore, the self-learning teacher’s to be important to increase student skills in her/his competence and mental of character that would affect on work culture.